Serum interleukin 1 and interleukin 10 levels in Iraqi leukemic patients with hepatitis G virus infection. - Alani, Muhammad M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background:Objectives : This prospective   study aimed to  estimate interleukins 1 and 10  levels in acute  hepatitis (G) in Iraqi patients with leukemiaHepatitis G virus and GB virus C (GBV-C)  RNA viruses that were independently identified in 1995, and were subsequently found to be two isolates of the same virus. Blood transfusion is the main risk factor for HGV transmission Immune-mediated mechanisms are believed to play an important pathogenic role in  hepatitis G virus infection. Interleukin-1 (IL-1) plays an important role in the inflammatory process. implying that IL-1 may play a role in viral clearance and  suggesting that IL-1 has direct antiviral activity, so  that IL-1 induces novel antiviral pathways within a cell. Interleukin 10 ( IL-10 )is secreted by T helper-2 type cells (Th2) which may down regulate cell-mediated immune effecter mechanisms important in the host defense against intracellular pathogens.Methods: This cross sectional study was carried out at the national center of hematology , almustansiriya University and department of  microbiology  in Baghdad  medical college in Baghdad, Iraq  from January till August  2012. The study involved 33 patients (19 males & 14 females) diagnosed with  hepatitis G infection as having a positive IgM antibodies by ELISA technique .Serum IL-1 and IL-10 levels were measured in 33  patients with  hepatitis G virus infection and 40 leukemia patients without HGV infections as a control group  by ELISA technique .Results: Twenty three  patients (70%) with hepatitis G infection  had elevated serum IL-1 alpha levels  (the normal detection level is below 5 pg/ml), the patient serum IL 1 alpha range 2-37 pg/ml, with a mean 27.813 and SD 32.765 ). There was also a high significant correlation   between serum IL-1 alpha  level and hepatitis G infection (p value= ± 0.004) when compared with the control group by the  t –test Also serum IL-10  level was below the normal detection limit (5-20 pg/ml) in 20  (60%) patients .The 33 patients  had  serum IL-10 levels (range 0.6 - 9 pg/ml, with a mean 2.213 & SD± 4.745 ) . There was a significant  correlation between serum IL-10 level & hepatitis G infection when compared with the control group (p